Active Earth Pressure Acting on Circular Shafts Using Numerical Approach - Abdelmajid Meftah; Naïma Benmebarek; Sadok Benmebarek (Civil Engineering Journal, 2022)
Retaining walls in axi-symmetric conditions and in plane strains have been widely treated in the literature using different approaches (limit equilibrium, limit analysis, slip line, and numerical techniques by finite elements or finite differences). The finite element or finite difference method provides more accurate solutions to the problem than the limit equilibrium method. In this paper, a new model of retaining wall in the axi-symmetry conditions under outward pressure is considered, this case can be widely used in the design of grain silos, buildings and road constructions. Numerical calculations using FLAC are reported to evaluate the evolution of the earth pressure distribution on a cylindrical wall filled with granular material and subjected to radial displacement. A parametric study is carried out in order to evaluate the distribution of the active earth pressure on the wall according to the radius, the angle of friction of the granular material, and the angle of friction of the interface granular material-wall. This study shows that there is an effect of the circular shape and the inclination of the wall on the active earth pressures. Doi: 10.28991/CEJ-2022-08-04-09 Full Text: PDF